2019
DOI: 10.1021/acs.jafc.9b03445
|View full text |Cite
|
Sign up to set email alerts
|

Improved Simple Sample Pretreatment Method for Quantitation of Major Human Milk Oligosaccharides Using Ultrahigh Pressure Liquid Chromatography with Fluorescence Detection

Abstract: Human milk oligosaccharides (HMOs) maintain and promote infant health. Most of the current methods for HMOs quantitation require labor-intensive and time-consuming steps for sample preparation. This study presents two very simple and easy-to-operate pretreatment methods, requiring either ultrafiltration or centrifugation to separate free oligosaccharides from whole fat human milk and other milk matrix before oligosaccharides labeling for quantifying HMOs using ultrahigh pressure liquid chromatography with fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 47 publications
1
25
3
Order By: Relevance
“…The data from these studies conducted in the Chinese population varied considerably. The results reported by Elwakiel et al, 2018 [ 1 ] were over twice as high as the results reported by Huang et al, 2019 [ 24 ] and Ma et al, 2018 [ 25 ] at each stage of lactation ( Table 3 ). This may be explained, at least in part, by the different analytical methodologies and the times of breast milk collection used to analyze HMOs.…”
Section: Composition Throughout Lactationmentioning
confidence: 51%
See 3 more Smart Citations
“…The data from these studies conducted in the Chinese population varied considerably. The results reported by Elwakiel et al, 2018 [ 1 ] were over twice as high as the results reported by Huang et al, 2019 [ 24 ] and Ma et al, 2018 [ 25 ] at each stage of lactation ( Table 3 ). This may be explained, at least in part, by the different analytical methodologies and the times of breast milk collection used to analyze HMOs.…”
Section: Composition Throughout Lactationmentioning
confidence: 51%
“…Given this study did not include the North region of China (e.g., Inner Mogolia/Hohhot), it is still unknown whether there may be any differences in the concentrations and composition of HMOs between different ethnic Chinese groups or populations with different dietary patterns (which have not been reported in the studies). It is important to note that the study by Austin et al, 2016 [ 32 ] only reported ten individual HMOs, therefore the total HMOs based on the sum of the ten individual HMOs were lower than any of the results reported by Elwakiel et al [ 1 ], Huang et al [ 24 ] and Ma et al [ 25 ] and cannot be directly compared ( Table 3 ).…”
Section: Composition Throughout Lactationmentioning
confidence: 89%
See 2 more Smart Citations
“…HMO 3′-GL is naturally present in human milk and was already isolated from human milk in 1988 [ 40 ]. Recently, a single chromatography run using an improved sample pre-treatment method and ultrahigh pressure liquid chromatography with fluorescence detection quantified 15 sialylated and neutral HMOs with high sensitivity, identifying 3′-GL and 6’-GL in colostrum, transitional, and mature human milk [ 108 ]. Human milk from mothers with preterm delivery revealed 3′-GL concentrations of 4–28.82 µg/mL (median 10.44) at 1 w postpartum, whereas concentrations ranged from 4–32.97 µg/mL (median 12.34) in colostrum and 4–20.73 µg/mL (median 4) at 8 w postpartum from mothers with term delivery [ 46 ].…”
Section: The ‘Biotic’ Family: Resembling Human Milk Benefits In Inmentioning
confidence: 99%